Use of smartphone and perception towards the usefulness and practicality of its medical applications among healthcare workers in Saudi Arabia - Mostafa A. Abolfotouh; Ala'a BaniMustafa; Mahmoud Salam; Mohammed Al-Assiri; Bader Aldebasi; Ibraheem Bushnak (BMC, 2019)
Abstract Background In Saudi Arabia, healthcare industry is undergoing major expansions to meet the demand of rapidly growing healthcare needs. The aims of this study were; (1) to assess the pattern of smartphone use in healthcare facilities, and (2) to determine perception towards its use among healthcare workers. Method A cross-sectional survey of 351 healthcare workers (HCWs) at King Abdulaziz Medical City (KAMC) in Riyadh, Saudi Arabia was conducted, from October to November 2016, using a previously validated perception domain to measure perception towards usefulness (5 statements) and practicality (5 statements) of smartphones in clinical settings. Pattern of use of smartphones and health-related applications in healthcare facilities was also investigated. Logestic regression models were applied to identify the predictors of smartphone use and installation of health-related applications for use in healthcare facilities. Significance was considered at p-value of < 0.05. Results Utilization rate of smartphone was 42.3%, and only 6.1% of all healthcare providers reported always using applications in their practice. Reasons for use were: as a source of drug information (69.8%), for disease diagnosis (56.4%), to access medical websites (42.5%), to review guidelines and protocols related to healthcare (34.1%), for procedure documentation (23.5%), and as a source of patients education materials (22.3%). Perceptions of HCWs towards smartphone use was less than satisfactory (Overall percentage mean score = 60.4 ± 18.7), with only 11.6% reporting positive perception. After adjusting for possible confounders, the total perception mean score was a significant predictor of both smartphone use (β = 0.033, p < 0.001) and medical applications installation (β = 0.033, p < 0.001). Installation of medical applications was also predicted by being a physician (β = 0.008, p = 0.024). Conclusion Smartphone utilization in healthcare facilities by HCWs in Saudi Arabia is low. This could be attributed to their less than satisfactory level of perception towards its use. Smartphone use and installation of medical applications for use in health facilities were predicted by perceived usefulness and practicality of its use. Intervention from higher health authorities is necessary to enforce the importance of smartphone use in clinical practice. Conduction of further studies on the impact of smart phone use on the healthcare quality in Saudi Arabia is recommended.